PENGARUH PROMOSI JABATAN DAN INSENTIF TERHADAP MOTIVASI KERJA PADA SEKRETARIAT DAERAH KABUPATEN MUSI BANYUASIN - Sawal Udin (Universitas Bina Taruna Gorontalo, 2022)
This study aims to determine the effect of promotion and incentives on work motivation at the Regional Secretariat of Musi Banyuasin Regency. The type of research used in this research is quantitative descriptive. The population in this study were employees of the Regional Secretariat of Musi Banyuasin Regency which opened 175 people. The sample in this study used the slovin formula as many as 122 people. Data collection techniques in this study used interviews, observation, library research and questionnaires. Data analysis using SPSS program. results Based on the analysis and discussion described, it can be concluded that the variable of job promotion has a significant effect on work motivation. This means that the promotion position has a positive effect on employees, the better the promotion, the higher the work motivation. Incentive variables have a significant effect on work motivation. This means that the higher the incentives received, the higher the work motivation. Together, the variables of Job Promotion and Incentives have a significant effect on Work Motivation. This means that with the Promotion of Positions and better incentives, it can motivate employees to work optimally and can achieve the goals of an organization.